A religião no processo psicoterapêutico - Campos, Alexsandra Fernandes (2007)
I have choosen as theme for this study the search of the sense for the life due to the religious experience and how it appears during the therapeutic process having as a theoretical and phennomelogy foundation. In order to achieve this objective I did not realize readings of authors in the psychological area only but also of texts of Christian authors. Having these readings as theoretical references, I make an analysis for understanding the importance of the religious values on the life modifications of the choosen study case, for my own reflection. As finalization, I emphasize the value of the meaning added to the holly as an affective process of changing